ARTICULATE STORYLINE MEDIA DEVELOPMENT OF TARIKH ISLAM LESSON IN MODERN ISLAMIC BOARDING SCHOOL DARUSSALAM GONTOR FOR GIRL - Dian Silvia Rozza; Khozin Khozin; M Nurul Humaidi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The problem that usually occurs in the learning process is the appearance of boredom dan laziness because the learning model used by the teacher seems monotonous. Teachers can overcome problems related to learning conditions through the use of learning media. This study aims to describe the development procedure and determine the feasibility of Articulate Storyline media in learning Tarikh Islam in Modern Islamic Boarding School Darussalam Gontor 2 Campus For Girls. This study uses a research and development approach with the Borg & Gall model. Data collection techniques with observation, interviews, documentation, and validation. Interviews were conducted with the responsible teacher of Class 1 Intensive. Observations were made in the learning process of the Class 1 Intensive. Documentation in photographs taken as concrete evidence of the learning process. Validation activities are carried out in three steps: preliminary field testing, main field testing, and operational field testing. Preliminary field testing involved a materials expert and a media expert. Main field testing involved ten students of Class 1 Intensive. Operational field testing involved 21 students of Class 1 Intensive. The data analysis techniques used are qualitative descriptive analysis and quantitative descriptive analysis. The result of this study indicates that the media development procedure has been carried out in a detailed and systematic way regarding the ten steps of the Borg & Gall model. The result also shows that the product of Articulate Storyline media development is very feasible when used in the learning process.